The translation of surgical animal models to human clinical research: A cross-sectional study. (May 2020) - Ruan, Yongle; Robinson, N. Bryce; Khan, Faiza M.; Hameed, Irbaz; Rahouma, Mohamed; Naik, Ajita; Oakley, Christian T.; Rong, Lisa; Girardi, Leonard N.; Gaudino, Mario
Abstract: Background: Surgical animal models are used in pre-clinical scientific studies. To date there has not been an analysis of how effective these data are when translated to human/clinical research. In this retrospective review, we evaluate the impact of studies using surgical animal models on human/clinical research through study-level analysis of citations. Methods: The top two ranking clinical journals based on impact factor for the top ten surgical specialties were identified and a search was run on PubMed to identify studies using surgical animal models published in the years 2007 and 2008. The translation to human/clinical research of each study was evaluated by analyzing the frequency of citation in human studies over the ten years following publication. Regression was used to identify predictors of citation in human/clinical research. Results: 411 animal studies using surgical models were identified. Over the course of the 10 years following publication the original animal studies were cited 6063 times, with 1300 (21.4%) citations in human/clinical studies and 4763 (78.6%) in animal/basic science studies. The median number of citations in human/clinical research was 1 (IQR 0–5). Regression showed an association between citation in human/clinical research and the use of porcine models and the specialties of general surgery, oral and maxillofacial surgery, orthopedic surgery, transplant, and plastic surgery. Conclusion: The use of animal models in surgical research shows poor translation to human/clinical research. Alternative surgical models should urgently be explored. Highlights: Translation of pre-clinical animal studies to human/clinical research has been questioned. Articles from the top two journals across 10 surgical specialties published between 2007 and 2008 containing a surgical animal model were reviewed. The translation to human/clinical research was evaluated by analyzing the frequency of citation in human studies over ten years. The translation of pre-clinical surgical animal model research to human/clinical research is poor.